Extending Extant Models of the Pathogenesis of Borderline Personality Disorder to Childhood Borderline Personality Symptoms: The Roles of Affective Dysfunction, Disinhibition, and Self-and Emotion-Regulation Deficits - Gratz, Kim L. (2009)
Although research has been conducted on the course, consequences, and correlates of borderline personality disorder (BPD), little is known about its emergence in childhood, and no studies have examined the extent to which theoretical models of the pathogenesis of BPD in adults are applicable to the correlates of borderline personality symptoms in children. The goal of this study was to examine the interrelationships between two BPD-relevant personality traits (affective dysfunction and disinhibition), self- and emotion regulation deficits, and childhood borderline personality symptoms among 263 children aged 9 to 13. We predicted that affective dysfunction, disinhibition, and their interaction would be associated with childhood borderline personality symptoms, and that self- and emotion-regulation deficits would mediate these relationships. Results provided support for the roles of both affective dysfunction and disinhibition (in the form of sensation seeking) in childhood borderline personality symptoms, as well as their hypothesized interaction. Further, both self- and emotion-regulation deficits partially mediated the relationship between affective dysfunction and childhood borderline personality symptoms. Finally, results provided evidence of different gender-based pathways to childhood borderline personality symptoms, suggesting that models of BPD among adults are more relevant to understanding the factors associated with borderline personality symptoms among girls than boys.